A Review of Gelatine Formulations for Topical Skin Cancer Treatment - Vaidya, Sunita N. (Asian Journal of Pharmaceutics (AJP), 2024)
Regarding both regional and widespread drugs, cancer of the skin, regardless of its manifestations, is the disease with the highest incidence rate in the world. Topical chemotherapy is an intriguing therapeutic approach due to its low cost and lack of invasiveness. Nonetheless, it is difficult to distribute antineoplastic drugs through the skin due to the numerous methodologies that have been utilized to ascertain the physicochemical features, including solubility, ionized molecular weight, and melting point, as well as the efficacy of the stratum corneum’s protective barrier, utilized to increase drug absorption, retention, and effectiveness. Its objectives are to determine the most popular methods for topical medication administration using gel-based medications for the treatment of skin cancer. The preparation methods, the excipients employed, and the techniques for characterizing gels are briefly explained. Safety considerations are also emphasized.